Assembly Design and Experiment of Silent Chain - Ding Song; Chi Chunyan; Shao Guiyang; Jiang Donglin; Xu Jing; Xiu Ruixian (Jixie chuandong)
In order to improve the service life of the silent chain,a new silent chain assembly method is proposed.The chain plate of clearance fit at the ends of pin and pad of interference fit are changed to outer chain plate of interference fit where the joint is locked with the circlip to improve the chain ability to withstand lateral impact.The extrusion force test is conducted on outer chain plate of interference fit and pad of interference fit,the test result shows that extrusion force of outer chain plate is 4.52 times that of pad.The shear force failure test is conducted on joint lock piece and the test result shows that the failed shear force of the s circlip is 3.87 times that of the 2×12cotter pin.The qualitative test of ten thousand kilometers of off-road vehicle shows that the silent chain installed with traditional method has to be repaired or replaced for every seven hundred kilometers while the silent chain with new assembly method does not fail due to falling off of the chain plate or extrusion of the joint.These two experimental results both prove the reasonableness of new assembly method for silent chain and effectiveness to withstand lateral impact.